Normalites : the first professionally prepared teachers in the United States - Kolodny, Kelly Ann (Contemporary research in education., 2014)
Normalites: The First Professionally Prepared Teachers in the United States is a new original work which explores the experiences of three women, Lydia Stow, Mary Swift and Louisa Harris, who were pioneers in the movement in teacher education as members of the first class of the nation's first state normal school established in Lexington, Massachusetts in 1839. The book is biographical, offering new insights derived from exceptional research into the development of the normal school movement from the perspectives of the students. While studies have provided analysis of the movement as a whole, as well as some of the leaders of the initiative, such as Horace Mann and Henry Barnard, there is a lack of rich, published information about the first groups of students. Understanding their accounts and experiences, however, provides a critical foreground to comprehending not only the complexity of the nineteenth century normal school movement but, more broadly, educational reform during this period.Arranged chronologically and in four parts, this book explores the experiences of Lydia Stow, Mary Swift and Louisa Harris during their normal school studies, their entrance into the world and commencement of their careers, the transitions in their personal and professional lives, and the building of their life work. Throughout these periods, their formal educational experiences, as well as broader moments of transformation, are considered and how life paths were shaped.This book will be of interest to undergraduate and graduate students and faculty connected to teacher preparation programs. More than 100,000 students are currently awarded baccalaureate degrees each year in Education. Over 80,000 of these students are women. Their experiences are rooted in the pioneering efforts of Lydia Stow, Mary Swift, and Louisa Harris at our nation's first state normal school. It is a particularly fitting time to share their experiences as the 175th anniversary of the start of formal, state sponsored teacher education, the normal school movement, will be celebrated in 2014.